Harmonium [videorecording (DVD)] - Fukada, Kōji, 1980-; Fukada, Kōji, 1980-; Furutachi, Kanji; Asano, Tadanobu; Tsutsui, Mariko, 1962- (Film Movement, 2017)
Toshio's family life collapses after he hires an old acquaintance just released from prison.